Monoclonal antibodies protect against pandrug-resistant Klebsiella pneumoniae - Roscioli, Emanuele; Zucconi Galli Fonseca, Vittoria; Bosch, Soraya Soledad; Paciello, Ida; Maccari, Giuseppe; Cardinali, Giulia; Batani, Giampiero; Stazzoni, Samuele; Tiseo, Giusy; Giordano, Cesira; Yuwei, Shen; Capoccia, Laura; et al. (Nature (London), 2025)
The ‘silent pandemic’ caused by antimicrobial resistance requires innovative therapeutic approaches. Human monoclonal antibodies (mAbs), which are among the most transformative and safe drugs in oncology 1 and autoimmunity 2 , are rarely used for infectious diseases and not yet used for antimicrobial resistance 3 . Here we applied an antigen-agnostic strategy to isolate extremely potent human mAbs against Klebsiella pneumoniae sequence type 147 (ST147), a hypervirulent and pandrug-resistant lineage that is spreading globally. Isolated mAbs target the KL64 capsule and the O-antigen. However, although mAbs displayed bactericidal activity in the picomolar range in vitro, only the capsule-specific mAbs were protective against fulminant bloodstream infection by ST147 and two geographically and genetically distant carbapenem-resistant KL64-bearing K. pneumoniae . Protection observed in vivo correlated with in vitro bacterial uptake by macrophages and enchained bacterial growth. Our study thus describes a mAb that protects against pandrug-resistant K. pneumoniae and provides a strategy to isolate mAbs and identify mAbs that confer protection against bacteria with antimicrobial resistance. Capsule-specific human monoclonal antibodies are protective against bloodstream infection by Klebsiella pneumoniae sequence type 147 in a mouse model of septicaemia, and could provide a useful strategy against pathogens with antimicrobial resistance.